The mechanical behavior of high-translucent monolithic zirconia after adjustment and finishing procedures and artificial aging - Hatanaka, Gabriel Rodrigues [UNESP]; Polli, Gabriela Scatimburgo [UNESP]; Adabo, Gelson Luis [UNESP] (Elsevier, 2019)
Statement of problem: How occlusal adjustments and finishing of high-translucent monolithic zirconia restorations affect their mechanical behavior is unclear. Purpose: The purpose of this in vitro study was to investigate the effect of grinding, finishing, and hydrothermal degradation on the roughness, flexural strength, and reliability of fully stabilized zirconia (FSZ)and partially stabilized zirconia (PSZ)for monolithic restorations. Material and methods: Specimens of PSZ and FSZ were divided into 5 groups: control (Ctrl); those ground by using coarse diamond rotary instrument (Gr); those that underwent grinding, polishing (diamond rubber), and glazing (GrPolGl); those that underwent grinding and glazing (GrGl); and those that underwent grinding and polishing (GrPol). These groups were subdivided into nonaged and hydrothermally aged in autoclave (134 °C, 200 kPa). Three-point bend tests (flexural strength [FS])were performed (n=30), and roughness (Ra)was measured by using a contact profilometer (n=30). The Weibull moduli were obtained from the FS data. The intergroup FS was analyzed by the Kruskal-Wallis test and Student-Newman-Keuls method, and the intragroup FS, Mann-Whitney tests (α=.05). Results: The median FS for PSZ (MPa)for the aforementioned groups is as follows: Gr (1147.8)=GrPol (1210.3)>GrPolGl (815.6)>GrGl (569.7)=Ctrl (583.0). The FS for FSZ (MPa)for the aforementioned groups is as follows: GrPolGl (404.2)=GrGl (427.0)<Ctrl (484.8)=Gr (435.9)=GrPol (443.7). Grinding led to high roughness values. The Weibull modulus was most influenced by glaze treatment. Conclusions: Monolithic zirconia exhibited a different mechanical behavior after adjustment procedures and hydrothermal aging. Grinding increased the roughness, and polishing reduced the roughness of the ground surface. FS improvement by finishing depended on the type of zirconia. Glazing smoothened the surface but tended to decrease the FS. Aging of PSZ improved the FS except in the control and glazed groups, whereas FSZ was not affected by aging, except in the GrGl group.